6’-sialyllactose ameliorates the ototoxic effects of the aminoglycoside antibiotic neomycin in susceptible mice - Abou Assale, Tawfik; Kuenzel, Thomas; Schink, Tamara; Shahraz, Anahita; Neumann, Harald; Klaus, Christine (Frontiers in Immunology, 2023)
Sialic acids are the terminal sugars of the cellular glycocalyx and are highly abundant in the nervous tissue. Sialylation is sensed by the innate immune system and acts as an inhibitory immune checkpoint. Aminoglycoside antibiotics such as neomycin have been shown to activate tissue macrophages and induce ototoxicity.In this study, we investigated systemic subcutaneous application of the human milk oligosaccharide 6'-sialyllactose (6SL) as potential therapy of neomycin-induced ototoxicity in postnatal mice. Systemic repeated treatment of mice with 6SL ameliorated the neomycin-induced hearing loss and attenuated the neomycin-triggered macrophage activation in the cochlear spiral ganglion. In addition, 6SL reverted the neomycin-mediated increase in gene transcription of the pro-inflammatory cytokine interleukin-1 (Il-1b) and the apoptotic/inflammatory kinase Pik3cd in the inner ear. Interestingly, neomycin application also increased gene transcription of the desialylating enzyme neuraminidase 3 (Neu3) in the inner ear. In vitro, we confirmed that treatment with 6SL has anti-inflammatory, antiphagocytic and neuroprotective effects on cultured lipopolysaccharide-challenged human THP1macrophages.Thus, data demonstrate that treatment with 6SL has anti-inflammatory and protective effects in neomycin-mediated macrophage activation and ototoxicity.